Improvement of Population Data for Kuta Mbelin Village, STM Hulu District, Deliserdang Regency to Open SID Based Population Data - Efendi, Syahril; Nurahmadi, Fauzan; Manik, Fuzy Yustika; Seniman; Harumy, T. Henny Febriana; Jaya, Ivan; Absah, Yeni; Syahputra, Muhammad Romi; Hastuti, Liana Dwi Sri; Nainggolan, Pauzi Ibrahim; Herianto, Tulus Joseph; Br Ginting, Dewi Sartika; Yudhistira (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program conducted in the fostered village of LPPM USU, namely Kuta Mbelin Village, STM Hulu District, Deliserdang Regency, which already has a village information system (https://s.id/kutambelin) as a manifestation of a digital village, should convert the population data processed conventionally into population data that can be integrated with the village's needs. This includes the ability to monitor population growth, facilitate correspondence and archiving, obtain village population statistics, and more. To improve this data, the fostered village team is implementing an open-source Village Information System, commonly known as Open SID. The data processed by the village using MS Excel covers two hamlets out of the three in Kuta Mbelin village. Hamlet I has 261 residents and Hamlet II has 532 residents, while Hamlet III is still being processed by the village operator. This existing population data needs to be refined and integrated into the Open SID-based population data platform by first performing data cleaning to ensure it can be incorporated into the village information system. The data entry process is continuously carried out by the LPPM USU community service team and village operators, involving USU MBKM KKN students in the village.